2010
DOI: 10.3141/2183-04
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Transit Trip Characterization and Travel Behavior Comprehension

Abstract: Trips need to be described and have always been characterized by various levels of abstraction. It varies from a simple label such as home-based work to complete itinerary with sociodemographic characteristics of the trip maker and household. The rationale behind such classifications is that planners and modelers recognize that the demand of transportation is highly differentiated. It is hoped that additional attributes would provide a more complete portrait of the demand and an improved understanding of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 17 publications
0
32
0
1
Order By: Relevance
“…Different measures regarding the variability of travel behaviors of transit users were proposed. Chu and Chapleau [11] indicated the use of advance statistics, sophisticated GIS analysis, visualization, and machine learning and data mining to show travel behavior of passengers. Mohamed et al [12] showed a way to deal with analyzing the temporal behavior of the travelers in a public transportation system to obtain relevant clusters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different measures regarding the variability of travel behaviors of transit users were proposed. Chu and Chapleau [11] indicated the use of advance statistics, sophisticated GIS analysis, visualization, and machine learning and data mining to show travel behavior of passengers. Mohamed et al [12] showed a way to deal with analyzing the temporal behavior of the travelers in a public transportation system to obtain relevant clusters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Chu and Chapleau used the term "anchor points" to define the places that a person repeatedly visits, which usually include residence, work, or study locations (21). They performed spatial aggregation by grouping stops within 50 m of each other to form a new node.…”
mentioning
confidence: 99%
“…Although clustering groups method has the capability to characterize trips based on the passengers' travel behaviour (Chu and Chapleau, 2010), clustering groups technique cannot capture the complexity of travel patterns . In addition, clustering method is based on temporal and spatial variables and does not reflect passengers' motivation for travelling, whereas a classification method based on trip purpose does (Kuhlman, 2015).…”
Section: Trip Purpose Inference Using Smart Card Datamentioning
confidence: 99%
“…However, trips that take place in the morning peak and have return trips in the evening peak were considered as work trips (Lee and Hickman, 2014). Chu and Chapleau (2010) and Lee and Hickman (2014) considered trips made with student cards and where the alighting for these trips were near schools or universities as education trips. In addition, trips that are at the end of the day, and not the only trips for corresponding passengers, are considered as home trips (Devillaine et al, 2012).…”
Section: Trip Purpose Inference Using Smart Card Datamentioning
confidence: 99%
See 1 more Smart Citation